2019
DOI: 10.3847/1538-4357/ab39e4
|View full text |Cite
|
Sign up to set email alerts
|

1ES 1927+654: An AGN Caught Changing Look on a Timescale of Months

Abstract: We study the sudden optical and ultraviolet (UV) brightening of 1ES 1927+654, which until now was known as a narrow-line active galactic nucleus (AGN). 1ES 1927+654 was part of the small and peculiar class of "true Type-2" AGN, which lack broad emission lines and line-of-sight obscuration. Our highcadence spectroscopic monitoring captures the appearance of a blue, featureless continuum, followed several weeks later by the appearance of broad Balmer emission lines. This timescale is generally consistent with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
187
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 143 publications
(203 citation statements)
references
References 90 publications
(105 reference statements)
16
187
0
Order By: Relevance
“…The very soft X-ray emission observed after the event, and the fact that the optical/UV flux decreases following a trend consistent with the t −5/3 behavior (Trakhtenbrot et al 2019) are in agreement with the TDE scenario (e.g., Komossa 2015;Auchettl et al 2017), while the re-brightening observed in the X-rays is very different from what is typically observed in TDEs. Interestingly, the behavior seen in 1ES 1927+654 might be consistent with recent hydrodynamic simulations of a debris stream colliding with an accretion disk (Chan et al 2019).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The very soft X-ray emission observed after the event, and the fact that the optical/UV flux decreases following a trend consistent with the t −5/3 behavior (Trakhtenbrot et al 2019) are in agreement with the TDE scenario (e.g., Komossa 2015;Auchettl et al 2017), while the re-brightening observed in the X-rays is very different from what is typically observed in TDEs. Interestingly, the behavior seen in 1ES 1927+654 might be consistent with recent hydrodynamic simulations of a debris stream colliding with an accretion disk (Chan et al 2019).…”
Section: Discussionsupporting
confidence: 83%
“…1ES 1927+654 is a type-2 AGN that was recently found to develop broad optical emission lines after an optical outburst (23 December 2017; Trakhtenbrot et al 2019). Following the changing-look event, we started an intense 450-day X-ray monitoring campaign, which includes observations from NICER (265 pointings), Swift (14) and XMM-Newton/NuSTAR (3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations